PENGARUH PEMBERIAN RANSUM DARI LIMBAH JERAMI PADI DAN ONGGOK MELALUI PERLAKUAN CAIRAN RUMEN TERHADAP PERFORMAN DOMBA - Akhadiarto, Sindu (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2009)
Decreasing of land for agriculture pushed the exploiting of agricultural and industrialby-products for feedstuffs. Rice straw and Ã¢â‚¬Å“onggokÃ¢â‚¬Â represent the by-products thatvery potential to use for feedstuffs. However these by-products have low digestionvalue for livestock. Therefore processing of the by-products before use is essensialto increase its quality. The experiment was conducted for 7 weeks to investigatethe effects of feeding diets containing rumen liquor treated-rice straw or rumenliquor treated-onggok on the performance of local male sheeps. Parametersmeasured were feed intake (g/head/day), weight gain (g/head/day), and feedconversion. Data from randomized complete block design were analized usingANOVA and if its showed significantly different contras ortogonal test was used.The result showed that the treatments significantly (P<0,05) affected feed intake,weight gain, and feed conversion. R2 and R3 treatments significantly (P<0,01)increased feed intake compared with R4 and R1 treatment, while between R2 andR3 treatments, and R1 and R4 treatments were not different. It can be concludedthat treament of rumen liquor to rice straw could improve its nutritive quality whichwas proved by good performance of sheeps fed diets containing rumen liquortreated rice straw.